Faktor-faktor Penggerak Tax Avoidance pada Perusahaan Sektor Finance di BEI : Arus Kas Operasi, Capital Intensity dan Umur Perusahaan - Dian Diantia (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
Tax avoidance remains a critical issue in corporate financial management, particularly in developing economies like Indonesia. Companies often implement various strategies to minimize tax obligations, raising concerns about fairness and compliance. This study aims to examine the effect of Operating Cash Flow, Capital Intensity, and Company Age on Tax Avoidance among finance companies listed on the Indonesia Stock Exchange (IDX) during the period 2018–2023. The research employs a quantitative approach using secondary data. A total of 14 companies were selected as samples through purposive sampling, resulting in 84 firm-year observations over six years. Data analysis was conducted using EViews 12 software and included descriptive statistics, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results indicate that Operating Cash Flow has no significant effect on Tax Avoidance, implying that the availability of operating cash is not a primary factor in a company’s tax avoidance strategy. In contrast, Capital Intensity shows a significant positive effect, suggesting that firms with higher fixed asset investments are more likely to engage in tax avoidance, possibly through depreciation and tax incentives. Additionally, Company Age has a negative effect on Tax Avoidance, indicating that older companies tend to avoid taxes less, likely due to higher compliance and increased regulatory scrutiny. These findings suggest that tax authorities should consider asset structure and firm age when formulating tax oversight strategies.